Rozważania o rozkładzie odległości od punktów kratowych w rozkładzie równomiernym - Harańczyk, Grzegorz; Sokołowski, Andrzej (The Distribution of Distance From Lattice Points in Uniform Distribution, 2009)
A search for probability distribution of distance to lattice points in the uniform distribution is presented in the paper. Probability functions for one and two dimensional cases have been derived analytically. For higher dimensions, Monte Carlo analysis is advised in order to approximate the distribution. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 17-23